THE NATIONAL AND CULTURAL CHARACTERISTICS OF THE REALIZATION OF THE CONCEPT OF "GREETING" IN ENGLISH, UZBEK, AND RUSSIAN LITERATURE - Khushmanova Shakhnoza Ibragimovna (Modern American Journals, 2025)
This article explores the cultural and national particularities in the depiction and use of the concept of "greeting" within English, Uzbek, and Russian literary traditions. By conducting a comparative literary analysis grounded in cultural linguistics and ethnopoetics, the study reveals how greetings in literary texts reflect broader socio-cultural values and historical contexts specific to each culture. The analysis identifies distinct linguistic expressions, narrative functions, and symbolic roles of greetings, illustrating the intersection of language, culture, and literature. Findings suggest that greeting rituals in literature not only function as social communicative tools but also serve as markers of identity and cultural norms. This study contributes to cross-cultural literary scholarship by highlighting the nuanced ways greetings reveal national character and cultural mindset.
Keywords: Greeting, cultural linguistics, English literature, Uzbek literature, Russian literature, national identity, ethnopoetics